Magnetohydrodynamic Voltage Recorder for Comparing Peripheral Blood Flow - Wu, Kevin J.; Gregory, T. Stan; Lastinger, Michael C.; Murrow, Jonathan R.; Tse, Zion Tsz Ho (Annals of biomedical engineering, 2017)
Blood flow is a clinical metric for monitoring of cardiovascular diseases but current measurements methods are costly or uncomfortable for patients. It was shown that the interaction of the magnetic field ( B 0 ) during MRI and blood flow in the body, through the magnetohydrodynamic (MHD) effect, produce voltages ( V MHD ) observable through intra-MRI electrocardiography (ECG), which are correlated with regional blood flow. This study shows the reproducibility of V MHD outside the MRI and its application in a portable flow monitoring device. To recreate this interaction outside the MRI, a static neodymium magnet (0.4T) was placed in between two electrodes to induce the V MHD in a single lead ECG measurement. V MHD was extracted, and integrated over to obtain a stroke volume metric. A smartphone-enabled device utilizing this interaction was developed in order to create a more accessible method of obtaining blood flow measurements. The portable device displayed a <6% error compared to a commercial recorder, and was able to successfully record V MHD using the 0.4T magnet. Exercise stress testing showed a V MHD increase of 23% in healthy subjects, with an 81% increase in the athlete. The study demonstrates a new device utilizing MHD interactions with body circulation to obtain blood flow metrics.